2021
DOI: 10.3389/fcimb.2021.780365
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity Comparison of Ceftazidime–Avibactam and Aztreonam–Avibactam Against Bloodstream Infections With Carbapenem-Resistant Organisms in China

Abstract: ObjectivesThe aim of this work was to investigate the activity of ceftazidime–avibactam (CZA) and aztreonam–avibactam (AZA) against bloodstream infections caused by carbapenem-resistant organisms (CROs).MethodsNon-duplicate CROs, including 56 carbapenem-resistant Escherichia coli (CR-Eco), 318 carbapenem-resistant Klebsiella pneumoniae (CR-Kpn), and 65 carbapenem-resistant Pseudomonas aeruginosa (CR-Pae), were collected using the Blood Bacterial Resistant Investigation Collaborative System (BRICS) program in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Recent surveillance data reported the lower MIC of AZA (MIC 90 = 0.5/4 mg/L) against CRE, especially for metallo-β-lactamase (MBL)-producing isolates ( Sader et al., 2021 ). Our previous data also showed that the MIC 90 of AZA was 1/4 mg/L, extending the observations for BSI CR-Kp ( Yu et al., 2021 ). In the present study, we found the decreased susceptibility mechanisms of AZAH-Kp strains isolated from patients without history of previous AZA exposure.…”
Section: Discussionsupporting
confidence: 85%
“…Recent surveillance data reported the lower MIC of AZA (MIC 90 = 0.5/4 mg/L) against CRE, especially for metallo-β-lactamase (MBL)-producing isolates ( Sader et al., 2021 ). Our previous data also showed that the MIC 90 of AZA was 1/4 mg/L, extending the observations for BSI CR-Kp ( Yu et al., 2021 ). In the present study, we found the decreased susceptibility mechanisms of AZAH-Kp strains isolated from patients without history of previous AZA exposure.…”
Section: Discussionsupporting
confidence: 85%
“…Also, 60% activity was identified against NDM-1 carbapenemase, which contradicts literature describing poor activity of CZA against MBL-producing organisms. 42 This discrepancy could be allocated to other undetermined mechanisms that need future validation.…”
Section: Discussionmentioning
confidence: 99%
“…A total of non-duplicate 318 BSIs-CRKP isolates were collected by Blood Bacterial Resistant Investigation Collaborative System (BRICS) program from 34 hospitals in 2019 in China ( Wei et al, 2021 ). Multi-locus sequence typing (MLST) was performed using the scheme of Pasteur database ( Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of 24 antibiotics (including CZA and AZA) were determined in our previous study ( Wei et al, 2021 ). Carbapenemase-producing isolates were further identified using modified Hodge test according to Clinical and Laboratory Standards Institute (CLSI) guidelines ( Clinical and Laboratory S, 2021 ).…”
Section: Methodsmentioning
confidence: 99%